Macrophages and cellular immunity in Drosophila melanogaster. Issue 6 (December 2015) - Gold, Katrina S.; Brückner, Katja
Highlights: The invertebrate Drosophila melanogaster is a powerful genetic model for blood cell development and immunity. Drosophila gives rise to two myeloid lineages. These share highly conserved features with the two vertebrate myeloid systems, which are (1) self-renewing tissue macrophages and (2) macrophages of the monocyte lineage. Self-renewing macrophages in Hematopoietic Pockets are regulated by local sensory neuron microenvironments, and other tissues and systemic cues. The Lymph Gland is a progenitor-based hematopoietic organ that is regulated by local and systemic regulatory signals. Drosophila macrophages function in immunity, development, and tissue homeostasis through (1) phagocytosis, (2) relay of local and systemic signals. (3) extracellular matrix deposition. Abstract: The invertebrate Drosophila melanogaster has been a powerful model for understanding blood cell development and immunity. Drosophila is a holometabolous insect, which transitions through a series of life stages from embryo, larva and pupa to adulthood. In spite of this, remarkable parallels exist between Drosophila and vertebrate macrophages, both in terms of development and function. More than 90% of Drosophila blood cells (hemocytes) are macrophages (plasmatocytes), making this highly tractable genetic system attractive for studying a variety of questions in macrophage biology. In vertebrates, recent findings revealed that macrophages have two independent origins: self-renewing macrophages, which reside and proliferate in local microenvironments in a variety of tissues, and macrophages of the monocyte lineage, which derive from hematopoietic stem or progenitor cells. Like vertebrates, Drosophila possesses two macrophage lineages with a conserved dual ontogeny. These parallels allow us to take advantage of the Drosophila model when investigating macrophage lineage specification, maintenance and amplification, and the induction of macrophages and their progenitors by local microenvironments and systemic cues. Beyond macrophage development, Drosophila further serves as a paradigm for understanding the mechanisms underlying macrophage function and cellular immunity in infection, tissue homeostasis and cancer, throughout development and adult life.